Improving the Quality of Public Services: The Role of Transformational Leadership, Organisational Culture, and Work Engagement - Andi Achmad Syukri; Tajuddin Malik; Mattalata; Kurniawty Sandra (Cendekiawan Indonesia Timur, 2025)
This study aims to analyse the effect of transformational leadership, organisational culture, and work engagement on the quality of public services by considering the mediating role of organisational commitment and apparatus performance in the Majene Regent's Office. This research is motivated by the challenge of improving the quality of public services through optimising apparatus performance and forming high organisational commitment. Quantitative approach was used in this study with survey method and data collection through questionnaires involving employees in Majene Regent Office. The results showed that transformational leadership, organisational culture, and work engagement have a significant influence on organisational commitment, apparatus performance, and public service quality. In addition, organisational commitment and apparatus performance are proven to act as mediating variables that strengthen the relationship between independent variables and public service quality. This research provides practical implications in the development of leadership strategies and organisational culture that support improved performance and quality of public services. The main contribution of this research is to provide empirical evidence on the importance of synergy between transformational leadership, organisational culture, and work engagement in building organisational commitment and improving apparatus performance, which in turn contributes to better public service quality.